Analysis of Madrasah Aliyah Teachers’ Difficulties in the Implementation of the Independent Learning Curriculum - Abdul Walid; Abdul Razzaq; Andi Kamal Ahmad (Universitas Muhammadiyah Barru, 2024)
The purpose of this study is to determine; the planning of the independent learning curriculum; the implementation of the independent learning curriculum; and the evaluation of the independent learning curriculum, the implementation of the independent learning curriculum for class X students at MAN Pinrang. This research method uses a qualitative approach with a descriptive research type. The subjects of this study were the principal, Mathematics Teachers of class X at MAN Pinrang. Data collection carried out in this study were Observation, Interviews, and Documentation. The data analysis techniques used were Data Reduction, Data Presentation, and Conclusion Drawing. The research results show that: the Independent Learning Curriculum provides flexibility for teachers in designing learning that suits the needs of students; implementation of the Independent Learning Curriculum at MAN Pinrang such as: Taking training, Collaborating with fellow teachers, Utilizing existing resources, and Innovating; evaluation of the Independent Learning Curriculum offers a more flexible and student-centered assessment approach such as a) Written tests, b) Oral tests c) Performance assessments d) use of rubrics, and e) Assessment scales.